Decisions and reasonings of top-class handball referees under physical load - Bloß, N.; Schorer, J.; Loffing, F.; Büsch, D. (German Journal of Exercise and Sport Research, 2022)
Correct decision-making under physical load is a central challenge for referees in sports games. Handball referees are assumed to make both a decision (calling a foul or no foul) and to call its reasonings (type of foul, punishments). However, the impact of physical load on these two aspects has not been differentiated so far. Here, in two studies, we aimed to investigate the hypothesised impact of physical load on both referees` decisions and reasonings. To this end, N= 66 (study 1) and N= 73 (study 2) top-class handball referees performed the Yo-Yo Intermittent Recovery Test combined with a video-based decision-making test. Referees` decisions improved from initial to medium physical load and they deteriorated under maximal physical load in study 1, whereas in study 2 the quality of the decisions was constant across physical load conditions. The percent of correct reasonings decreased from initial to medium physical load in study 1, whereas the opposite pattern was found in study 2. In both studies, reasoning performance did not change from medium to maximal physical load. Moreover, referees demonstrated better endurance performance in study 2 than in study 1. Despite some methodological limitations (e.g. familiarisation with the experimental setup in referees who participated in both studies), the present findings tentatively indicate that a well-trained endurance capacity may support referees` decision-making, i.e. to make correct decisions and reasonings. Specifically, enhanced endurance capacity may lead to lower subjectively perceived fatigue, resulting in larger cognitive capacities that may facilitate referees` decision-making.